Invasive pulmonary aspergillosis with brain dissemination in an immunocompetent host - Kumar, Senthil (Autops Case Rep, 2021)
Invasive aspergillosis is an uncommon infection, which is mainly seen among immunocompromised patients. In recent years, cases of aspergillosis involving immunocompetent hosts are increasingly being reported. Herein, we report the case of a 27-year-old man with fever, productive cough, shortness of breath, and left hemiparesis. He had suffered trauma to his head 25 days prior. Imaging of the chest showed bilateral cavitary lesions in the lungs, and neuroimaging revealed a space-occupying lesion in the right frontoparietal cerebrum. He was suspected of having an abscess or metastasis. He died on day 3 of hospitalization, and an autopsy was performed. The autopsy revealed the cause of death to be invasive pulmonary aspergillosis, with brain dissemination. Invasive aspergillosis is uncommon in apparently immunocompetent individuals, and we discuss the autopsy findings in detail.